Responsible Leadership Behaviours among Human Resource Managers in the South African Hybrid Work Context - Asoba , Samson Nambei; Mefi, Nteboheng Patricia (Journal of Ecohumanism, 2025)
This study explored the responsible behaviours among human resource managers in South Africa in the hybrid context with particular focus on their weaknesses and their areas of development. The study adopted the interview method of data collection following the need to have in-depth understanding of responsible leadership. Evidence from the study supports the literature findings that while leaders may have various strengths, they can benefit from more training and training as well as coaching sessions offered by their organisations. Areas of development included improving cultural intelligence. ICT skills training as well as strategies for applying the various concept of the Competency Assessment for Responsible Leadership (CARL) framework. Organisations are recommended to increase initiatives to improve responsible leadership in their organisations.